Risks of ovarian, breast, and corpus uteri cancer in women treated with assisted reproductive technology in Great Britain, 1991-2010: data linkage study including 2.2 million person years of observation. (11th July 2018) - Williams, Carrie L; Jones, Michael E; Swerdlow, Anthony J; Botting, Beverley J; Davies, Melanie C; Jacobs, Ian; Bunch, Kathryn J; Murphy, Michael F G; Sutcliffe, Alastair G
Abstract: Objective: To investigate the risks of ovarian, breast, and corpus uteri cancer in women who have had assisted reproduction. Design: Large, population based, data linkage cohort study. Setting and participants: All women who had assisted reproduction in Great Britain, 1991-2010, as recorded by the Human Fertilisation and Embryology Authority (HFEA). Interventions: HFEA fertility records for cohort members were linked to national cancer registrations. Main outcome measures: Observed first diagnosis of ovarian, breast, and corpus uteri cancer in cohort members were compared with age, sex, and period specific expectation. Standardised incidence ratios (SIRs) were calculated by use of age, sex, and period specific national incidence rates. Results: 255 786 women contributed 2 257 789 person years' follow-up. No significant increased risk of corpus uteri cancer (164 cancers observed v 146.9 cancers expected; SIR 1.12, 95% confidence interval 0.95 to 1.30) was found during an average of 8.8 years' follow-up. This study found no significantly increased risks of breast cancer overall (2578 v 2641.2; SIR 0.98, 0.94 to 1.01) or invasive breast cancer (2272 v 2371.4; SIR 0.96, 0.92 to 1.00). An increased risk of in situ breast cancer (291 v 253.5; SIR 1.15, 1.02 to 1.29; absolute excess risk (AER) 1.7 cases per 100 000 person years, 95% confidence interval 0.2 to 3.2) was detected, associated with an increasing number of treatment cycles (P=0.03). There was an increased risk of ovarian cancer (405 v 291.82; SIR 1.39, 1.26 to 1.53; AER 5.0 cases per 100 000 person years, 3.3 to 6.9), both invasive (264 v 188.1; SIR 1.40, 1.24 to 1.58; AER 3.4 cases per 100 000 person years, 2.0 to 4.9) and borderline (141 v 103.7; SIR 1.36, 1.15 to 1.60; AER 1.7 cases per 100 000 person years, 0.7 to 2.8). Increased risks of ovarian tumours were limited to women with endometriosis, low parity, or both. This study found no increased risk of any ovarian tumour in women treated because of only male factor or unexplained infertility. Conclusions: No increased risk of corpus uteri or invasive breast cancer was detected in women who had had assisted reproduction, but increased risks of in situ breast cancer and invasive and borderline ovarian tumours were found in this study. Our results suggest that ovarian tumour risks could be due to patient characteristics, rather than assisted reproduction itself, although both surveillance bias and the effect of treatment are also possibilities. Ongoing monitoring of this population is essential.